Anesthetic Management Of Peritonitis And Septic Shock In Colorectal Cancer: A Case Report - Rusli, Joseph; Sugiaman, Angela Mulyana; Gunadi, Julia Windi (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2025)
A 64-year-old male presented with signs of peritonitis, including severe abdominal pain, distension, and dehydration. Laboratory findings showed elevated inflammatory markers (leukocyte count: 19,500/mm³, C-reactive protein: 25 mg/dL), impaired renal function (serum creatinine: 2.1 mg/dL), and metabolic acidosis (pH: 7.25, lactate: 4.5 mmol/L). Imaging revealed a perforated rectal tumor with extensive peritoneal contamination. Emergency exploratory laparotomy was performed, involving tumor resection, colostomy formation, and peritoneal lavage. Hemodynamic instability due to septic shock was managed with norepinephrine to maintain blood pressure. Dobutamine was used to enhance cardiac output, while nitroglycerin supported coronary perfusion to prevent ischemic complications. Postoperatively, the patient required intensive care, including ventilatory support, fluid resuscitation, and tailored antibiotic therapy. Despite complications such as transient paralytic ileus, the patient was extubated on day five and discharged to the general ward by day ten. This case emphasizes the importance of early diagnosis, prompt surgical intervention, and personalized hemodynamic management in malignant-associated peritonitis. Multidisciplinary collaboration is critical to optimizing outcomes. Limitations of this case include its single-patient design. Further research should focus on advanced diagnostic tools and tailored resuscitation protocols to improve the management of similar cases.